(untitled) - MACUROVA, Anna; MACURA, Dusan (Trends in education, 2009)
In the paper are the graphic representations of the solutions some differential equations first order. Graphs are constructed by using DERIVE.
Keywords: solution of the differential equation; graphic representation; differential equation.